Implementasi Kurikulum Merdeka Belajar dalam Perspektif Islam - Dinata, Febrian; Hadi, Saputra; Mabrur, M.; Syaifudin, Muhammad (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to find out how to implement the independent learning curriculum in an Islamic perspective. This research is Library Research (library), aims to collect data and information from books, magazines, documents, records, and historical stories and other stories, the data collection technique used is the documentation technique. The analysis in this study uses content analysis or content analysis. Content analysis will produce a conclusion regarding the language style of the book, ideas in the contents of the book and grammar. Based on the results of the research, it can be concluded that the implementation of the independent learning curriculum in an Islamic perspective, provides guidance to students for independent learning, and has high creativity, by increasing solidarity, as well as establishing hospitality and in the implementation of independent learning, there is an ethos of fastabiqul khairat (competition in virtue) that must be cultivated.